Changes in Serum Lipids and Blood Glucose in Non Diabetic Patients with Metabolic Syndrome after Mixed Meals of Different Composition - Adriana Branchi; Adriana Torri; Cristina Berra; Emanuela Colombo; Domenico Sommariva (Journal of Nutrition and Metabolism)
Aims. To investigate the postprandial changes in serum lipoproteins and blood glucose and to verify whether different nutrient composition of the meal elicits different response in patients with (MetS+) and without (MetS−) metabolic syndrome. Research Design and Methods. 50 MetS+ patients and 50 age- and sex-matched MetS− consumed a regular lunch chosen among those more similar to their usual diet. Blood was drawn in the morning after 12-hour fasting and 2 and 4:30 hours after the meal. Results. Serum triglycerides increased more in MetS+ (35%, 4:30 hours after the meal) than in MetS− (29%), HDL-cholesterol decreased 2 hours after the meal in both groups (−4% and −5%, resp.). Blood sugar similarly increased in both groups (19%, 2 hours after the meal in MetS+ and 17% in MetS−) and plasma insulin increased more and remained high longer in MetS+ (73.5 and 52.3 μU/mL, 2 and 4:30 hours after the meal) than in MetS− (46.7 and 21.6 μU/mL). Difference in nutrient composition of the meal (carbohydrate 57%, fat 28% versus carbohydrate 45%, fat 35%) was not associated with differences in postprandial levels of triglycerides, HDL-cholesterol, glucose, and insulin within each group. Conclusions. As compared with MetS−, MetS+ patients show a greater hypertriglyceridemic and hyperinsulinemic response to a regular lunch whatever the carbohydrate or fat content of the meal.